Koleksyen Cherita Bala Nembiak Ari Kampung Sampun Gerunggang - Athirah, Azhar; Dolly, Paul Carlo (UNIMAS Publisher, 2024)
The present generation tends to gravitate towards spending their time on electronic devices, engaging in activities such as browsing social media or playing games, regardless of whether they reside in rural or urban areas. Children who cultivate a habit of reading not only enhance their communication and language skills but also play a pivotal role in mitigating the illiteracy rate among Malaysian children. Access to learning resources and experiences should be extended to all, including those in rural areas. The Program Pandey Baca specifically targets children living in longhouses. While formal education occurs within the school setting, it is our collective responsibility to ensure the holistic education of children in the Malaysian nation. Relying solely on formal education is inadequate for children in rural areas. The primary objectives of this programme are to instill a culture of reading among children and to establish dedicated spaces with accessible reading materials for both children and the surrounding community. Throughout this six-month project, various activities have been implemented, encompassing reading, writing, numeracy, storytelling, self-expression, drawing, and acting. The promotion of moral values is also a core focus integrated into all programme activities.